Penerapan Model First-Order Autoregressive Error dalam Analisis Daya Saing Ekspor Crude Palm Oil Indonesia Tahun 1995-2021 - Japany, Adham Malay; Dino Pardede, Marsandhi Evan; Humaira, Rania; Yuliana, Rita (Seminar Nasional Official Statistics, 2023)
Indonesia's Crude Palm Oil (CPO) commodity has advantages and has the potential to increase the country's economic growth. Indonesia is the largest CPO exporter in the world. However, in recent years CPO exports have continued to fluctuate. The potential and capability must be followed by quality improvement, so that later it can have an active role in international trade. Therefore, this study aims to identify an overview and analyze the factors that affect the competitiveness of Indonesia's CPO commodity exports in the world market. This study uses time series data from 1995 to 2021. The competitiveness analysis approached by Revealed Comparative Advantage (RCA) applies the first-order autoregressive error model method. The results show that during the 1995-2021 period, the competitiveness of CPO exports and CPO production tends to experience a positive trend, FDI tends to experience a negative trend, and real exchange rates tend to fluctuate. Furthermore, real exchange rates and CPO production affect the level of competitiveness of Indonesia's CPO exports.